Identification of Community-Based Football Activities in Yogyakarta: A Philosophical Review - Andhika Djalu Sembada (Institut Teknologi Bandung, 2025)
Football is not always professional and is not entirely competitive or achievement- oriented. Football can also be carried out as a recreational activity. Community- based football, more familiarly known as fun football, represents football activities that are recreational in nature. This study aims to identify the philosophical values contained in community-based football activities in Yogyakarta. Using a qualitative-philosophical approach (ethnography, phenomenology, hermeneutics), this study explores how community football is not only understood as a physical activity but also as a medium for reflecting humanistic values, solidarity, and local identity. Data were collected through participatory observation, in-depth interviews with respondents (consisting of players, coaches, team administrators, and field managers), as well as text analysis from relevant documents. The research results show that community football in Yogyakarta contains philosophical values such as mutual cooperation, togetherness, and happiness. This activity also serves as a space for negotiation between local traditions and modernity, which can have a positive impact on the sports tourism sector. The study concludes that community- based football in Yogyakarta is a social practice rich in philosophical meaning, as well as a form of resistance to the commercialization of sports. Keywords: philosophical, community, football, yogyakarta.